Verification of the ability of Cu to dissolve in BCC δ in a δ-γ Solid Solution above 1200 °C and boosting δ nano-hardness in Cu-containing PHSS. (1st April 2022) - Gan, Neng-Hao; Sun, Yi-Hsuan; Tsao, Tzu-Ching; Li, Chia-Lin; Liu, Jia-Heng; Yen, Hung-Wei; Hsueh, Chun-Hway; Yang, Jer-Ren; Wang, Shing-Hoa; Yeh, Jien-Wei; Chang, Horng-Yi; Hou, Wen-Hsing
Abstract: Because Cu is an austenite γ stabilizer, it is thought that Cu only dissolves in the FCC γ phase but not in the BCC δ when Cu-containing PHSS are treated in a dual δ-γ solid solution at high temperature. However, the nano precipitation of Cu in the allotriomorphic δ found upon quenching from 1295°C. To study this unexpected phenomenon, thermodynamic calculations were performed. The predicted solubilities of Cu in the γ and δ at 1295°C were 3.52 and 1.99 wt%. Consequently, quenching the solid solution from 1295 to 25°C results in the ultra-supersaturation of Cu in the δ. The vacancy concentration in the δ solution was estimated to change from 10 24 vac./m 3 at 1295°C to10 5 vac./m 3 at 25°C; quenching yields excess vacancies. Thus, Cu-rich nanoparticles precipitate in the δ matrix through the interdiffusion of the ultra-supersaturated Cu and excess vacancies. Graphical abstract: Image, graphical abstract